Market access and the arrow of time - Klein, Marius; Rauch, Ferdinand (AWI discussion paper series, 2023)
We revisit the natural experiments of division and unification of Germany now that more time has passed and more data have become available. We show that local market access shocks are not symmetric in time. The negative shock to local market access following the division of Germany lead to a fast and strong downward adjustment of the size of West-German cities near the new border. In contrast, the positive shock of reunification did not lead to any change in their relative size, even three decades after the German reunification.